Evaluation of the Peri-Implant Tissues of Patients with Severe Bone Atrophy Treated with a New Short and Extra-Short Implant System—A Pilot Study - Kely Cristina de Moraes; Geninho Thomé; Flávia Noemy Gasparini Kiatake Fontão; Carolina Accorsi Cartelli; Rosemary Adriana Chierici Marcantonio; Carolina Mendonça de Almeida Malzoni; Elcio Marcantonio Junior (Journal of Functional Biomaterials, 2024)
This study aimed to assess clinical and radiographic outcomes, including implant survival, marginal bone loss, and patient satisfaction, in individuals with severe bone atrophy treated using a newly developed system of short and extra-short implants. A total of 44 implants (37 short and 7 extra-short) were placed with immediate loading in 11 patients. The patients were followed up at between 6 and 24 months. Bone changes, keratinized mucosa, bleeding on probing, probing depth, crown-to-implant ratio, and patient satisfaction were evaluated. An implant survival and success rate of 100% was observed. The peri-implant bone condition showed no significant associations between marginal bone loss (MBL) and gingival recession. In extra-short implants, the crown-to-implant ratio did not affect MBL in the evaluated times. However, short implants showed a statistically significant inverse correlation between mesial measurement and crown-to-implant ratio (p = 0.006) and between distal measurement and crown-to-implant ratio (p = 0.004) over six months. Plaque was present in the mesiobuccal regions in 38.64% of the implants, with extra-short implants having the highest relative frequency (71.4%). Bleeding was observed in 18.9% of the short implants in the mesiolingual region and 14.3% of the extra-short implants. There was a statistically significant association between bleeding on probing in the mesiobuccal region and the type of implant (p = 0.026). The analysis of probing depth showed no difference between the types of implants. Within the limits of this study, short and extra-short implants presented similar clinical and radiographic behavior of soft and hard tissues in the evaluated times.